KEBERTERIMAAN DAN KETEPATAN MAKNA ISTILAH BIDANG KIMIA DI KALANGAN MAHASISWA FAKULTAS MIPA (The Acceptance and Accuracy of Meanings of Chemistry Terminology among Math and Natural Science Faculty Students) - Wiwiek Dwi Astuti (SAWERIGADING, 2014)
This reseaarch analyzes the acceptance and accuracy of meaning of the chemistry terminology resulted by Mabbim (Majelis Bahasa Brunei Darussalam-Indonesia-Malaysia) among the students of chemistry department in math and natural science faculty. Qualitative method is used to expose and explain the accuracy of the terminology in order to get the opinion of the respondents about the acceptance of the terminology itself because one of the characters of terminology is the accuracy, while, quantitative method is used to explain the level of the acceptance of the loan words and the translated words. In general, the loan and the translated words of terminology are accepted differently. It is proven by the questioner result which shows that more respondents choose score 3 compared with the loan words, then, the percentage shows 59.11% choose loan words and 38.89% chose the translated words. The significance value 0.05 in the remark column means that the chemistry terminology is accepted while significance value 0.05 means that terminology is unacceptable. In the aspect of meaning accuracy, the chemistry terminology, whether loan or translated shows different acceptance. It is proven by the questioner result which shows that more respondents choose score 3 to the loan words compared with translated words. The percentage shows that 50.46% choose loan words and 37.14% chose the translated words.